Characterization of the complete chloroplast genome of ornamental plant, Bougainvillea peruviana (Nyctaginaceae). Issue 3 (2nd July 2020) - Liu, Guofeng; Lee, Shiou Yih; Hu, Xing; Sun, Miaomiao; Ni, Jianzhong; Wang, Wei; Dai, Seping; Ruan, Lin
Abstract: Bougainvillea peruviana is a widely domesticated ornamental plant species. However, studies on B. peruviana are limited. In this study, we reported the complete chloroplast (cp) genome of B. peruviana . The cp genome is 154, 465 bp in length, containing a large single-copy (LSC) of 85, 563 bp and a small single-copy (SSC) of 18, 050 bp, which are separated by a pair of inverted repeats (IRs) of 25, 426 bp, each. A total of 132 genes, including 86 protein-coding genes, 38 tRNA genes, and eight rRNA genes, were predicted. The overall GC content for the cp genome is 36.5%. The maximum-likelihood tree constructed based on cp genome sequences showed that B. peruviana is placed under Nyctaginaceae and is diverged before Bougainvillea glabra and Bougainvillea spectabilis under strong bootstrap support.